Overcoming The Constitutional Silence: Insights from India to Fortify Sri Lanka’s Right to Education - Akash Dinendra, W.M.N. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Education is the main source of human capital and democratic empowerment, but the constitutional framework of Sri Lanka does not guarantee it to be a fundamental right. Even though the social indicators are progressive, the lack of an explicit Right to Education (RTE) in the 1978 Sri Lankan Constitution causes a gap in the structure that impedes equitable access and judicial protection. This work explores how constitutional and legislative changes in India can serve as a model for Sri Lanka, where the introduction of Article 21A and the Right of Children to Free and Compulsory Education Act, 2009 have made education a right that can be enforced through the law. The work uses qualitative comparative doctrinal methods and analyses constitutional provisions, legislation, case law, and international obligations under the ICESCR and CRC. For example, Indian cases like Mohini Jain v State of Karnataka (1992) and Unnikrishnan J.P. v State of Andhra Pradesh (1993) recognized education as an implicit right within Article 21, the right to life opening the door for the 86th Constitutional Amendment. In comparison, the Sri Lankan Article 27(2)(h) merely suggests that the state should promote education and is silent in terms of enforceability. This absence of a constitutional provision restricts judicial activism and, at the same time, the most vulnerable groups, particularly children in rural areas and estate sectors, are left without sufficient protection. The findings show that adding a clear Right to Education (RTE) to the Sri Lankan Constitution, together with a national education law inspired by India’s Constitution, would help improve accountability, ensure inclusion, and support Sri Lanka’s progress towards achieving Sustainable Development Goal 4. The paper ends with the assertion that education must be part of the constitution to guarantee both equity and quality and to make the transition of state obligation into citizen entitlement binding in law.
Keywords: Right to education; Sri Lanka constitution; India; Article 21A; Judicial activism